Automatic evaluation of tumor budding in immunohistochemically stained colorectal carcinomas and correlation to clinical outcome - Weis, Cleo-Aron Thias; Kather, Jakob Nikolas; Melchers, Susanne; Al-ahmdi, Hanaa; Gaiser, Timo (Diagnostic pathology, 2018)
Tumor budding, meaning a detachment of tumor cells at the invasion front of colorectal carcinoma (CRC) into single cells or clusters (<=5 tumor cells), has been shown to correlate to an inferior clinical outcome by several independent studies. Therefore, it has been discussed as a complementary prognostic factor to the TNM staging system, and it is already included in national guidelines as an additional prognostic parameter. However, its application by manual evaluation in routine pathology is hampered due to the use of several slightly different assessment systems, a time-consuming manual counting process and a high inter-observer variability. Hence, we established and validated an automatic image processing approach to reliably quantify tumor budding in immunohistochemically (IHC) stained sections of CRC samples.
Gesehen am 24.01.2019